430 views
1 vote
-4x-2(8x+1)=-(-2x-10)

User Paramore
by
5.5k points

1 Answer

3 votes
-4x - 2(8x + 1) = -(-2x - 10)

The first step is to distribute. On the left side of the equation, multiply the -2 by both terms inside the parentheses; on the right side of the equation, multiply the -1 by both terms inside the parentheses:

-4x - 2(8x + 1) = -(-2x - 10)
-4x - 16x - 2 = 2x + 10

Next, combine like terms.

-4x - 16x - 2 = 2x + 10
-20x - 2 = 2x + 10

Then subtract 2x from both sides and add 2 to both sides to get like terms together; combine like terms.

-20x - 2 = 2x + 10
-20x - 2x = 2 + 10
-22x = 12

Lastly, divide both sides by -22 and simplify.

-22x = 12
x = 12/-22
x = -6/11

Answer:
-6/11
User Neoraptor
by
6.0k points